The diagnostic and therapeutic value of Gastrografin in small bowel obstructions - Tutino, Roberta; Cavaglià, Mariachiara; Pipitone Federico, Nicoletta Sveva; De Simone, Veronica; Deiro, Giacomo; Gallo, Gaetano; Santarelli, Mauro (Frontiers in Surgery, 2025)
PurposeSmall bowel obstructions represent a major cause of hospitalization, morbidity and mortality in surgical emergency departments. The Gastrografin protocol could be an effective tool in facilitating its evaluation and treatment.MethodsA prospective observational study was conducted on patients admitted to the emergency department with a diagnosis of small bowel obstruction treated with the Gastrografin challenge to analyze risk factors related to the outcome.Results55 patients were included. In 38 patients (69.09%) the resolution of the occlusive condition was obtained. The progression of Gastrografin in the colon at x-ray was correlated to the positive outcome (p = 0.001). Older (>75 years old) and frailer patients were related to protocol failure and submitted more to surgery (p = 0.043; p = 0.022). Air-fluid levels at x-ray was related to negative outcome (P = 0.027). Higher doses of Gastrografin (100 ml vs. 50 ml) seems unrelated to obstruction resolution. At the two-year follow-up, among the 38 patients who tested positive, 8 patients (21.05%) had further access to the emergency department due to intestinal obstruction and were re-treated conservatively.ConclusionsThe standardized diagnostic-therapeutic protocol with Gastrografin is a valid tool in the non-operative management of small bowel obstructions offering a resolution of the obstructive condition in 70% of patients.